Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10853-021-06407-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the influence of surface characteristics on de-icing evaluation

Abstract: A comparative study of de-icing evaluation methods was conducted in this work, and their variations in response to surface characteristics were investigated. The mechanical de-icing measurements include centrifugal, push, and tensile methods. The centrifugal and the horizontal push (shear) methods suggested a linear relationship of ice adhesion strength with surface roughness, whereas the tensile (normal) method indicated an inverse curvilinear relationship with contact angle hysteresis. A partial correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The experimental results of shear adhesion strength studied by the authors and other scholars were also described in the graph. 27,31,35 It could be found that the range of variation of shear adhesion strength was significantly larger, with a difference of more than 15 times between the maximum and minimum values. On the one hand, various icing conditions results in differences in adhesion strength.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The experimental results of shear adhesion strength studied by the authors and other scholars were also described in the graph. 27,31,35 It could be found that the range of variation of shear adhesion strength was significantly larger, with a difference of more than 15 times between the maximum and minimum values. On the one hand, various icing conditions results in differences in adhesion strength.…”
Section: Resultsmentioning
confidence: 97%
“…26 Memon used the same apparatus to investigate the effect of surface wettability and roughness on the normal adhesion strength. 27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in heating duration indicates that there would be change in the overall initial ice adhesion force F at the ice/solid interface area; the residual adhesion force F 0 can be determined by Equation (). [ 47 ] F0=(FFm)δ$$F_{0} = \left(\right. F - F_{\text{m}} \left.\right) \cdot \delta$$where F m shows the reduced value of ice shear strength at the melting area.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in heating duration indicates that there would be change in the overall initial ice adhesion force F at the ice/solid interface area; the residual adhesion force F 0 can be determined by Equation ( 6). [47] F…”
Section: Electrothermal Heating Deicing Evaluationmentioning
confidence: 99%